Effect of Cetane Number on Specific Fuel Consumption and Particulate Matter and Unburned Hydrocarbon Emissions from Diesel Engines. (31st October 2012) - Cataluña, Renato; da Silva, Rosangela
Abstract : This paper discusses the effect of ignition delay time in diesel engines on the formation of particulate matter, using fuel formulations with different sulfur concentrations from various sources. Our findings indicate that the cetane number has a significant influence on particulate matter emissions, especially in engines with mechanical fuel injection. The maximum pressure in the combustion chamber increases as the cetane number increases, favoring the increase in the cracking reactions of high molecular weight fractions remaining in the liquid state and thus increasing the production of particulate matter. In certain conditions, this increase in pressure has a beneficial effect on the thermal efficiency of the cycle. Higher temperatures in the combustion chamber augment the speed of oxidation, reducing unburned hydrocarbon emissions. The ignition delay time of fuel has a strong effect on the formation of particulate matter and on the emission of unburned hydrocarbons.